Creating Porous Hydrogel Scaffolds using Templating Alginate Microspheres - Fiedler, Matt (My University, 2012)
Some of the greatest areas of advancement in the medical field are currently in areas such as tissue engineering, implant fixation, and drug delivery techniques involving the use of scaffolds. A scaffold is an artificial three dimensional porous structure that can support tissue formation within the body. For scaffolds to be most successful, they should have monodisperse pores, interconnected pores, a highly ordered microstructure, and controllable pore size. To accomplish this task, templating alginate microspheres were created using microfluidics and then packed into a microchannel. A UV polymerizable hydrogel was then flowed over the alginate spheres and polymerized. After the polymerization, the alginate spheres were removed using EDTA so that a porous hydrogel scaffold can be obtained. This process was successful as a proof of concept, but there are still details that need to be improved.
Thesis (Master's)--University of Washington, 2012
Keywords: Mechanical engineering; Mechanical engineering